The Influence of Liquidity and Leverage on Financial Distress With Profitability as Moderating Variables in Property and Real Estate Companies Listed on The IDX Period 2019-2023 - MASRUROH, Imas; SANUSI, Fauji; PURBASARI, Intan (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to examine the effect of Liquidity and Leverage on Financial Distress with Profitability as a moderating variable in property and real estate companies listed on the Indonesia Stock Exchange during the 2019–2023 period. This study is quantitative research using documentation techniques to collect data derived from company financial statements. The population in this study includes all property and real estate companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The sample consists of 10 companies out of a total of 59, selected using purposive sampling. The analytical tool used in this study is IBM SPSS 25.0, and the analysis technique employed is Moderated Regression Analysis (MRA). The results show that Liquidity has a significant positive effect on Financial Distress, Leverage has no significant effect on Financial Distress, Profitability is able to moderate the effect of Liquidity on Financial Distress, and Profitability is not able to moderate the effect of Leverage on Financial Distress.